Diabetes Mellitus and Regenerative Medicine: New Possibilities for the Regeneration of β Cells and Treatment of Diabetic Foot Ulcer - Nicola Daniele; Silvia Franceschilli; Fulvia Fraticelli; Francesco Zinno (Annals of Cytology and Pathology - Peertechz Publications, 2016)
Diabetes mellitus is a very common disease that affects a large number of people in the world and whose treatment is very expensive, also due to its complications. Diabetes is associated with many complications and among them the formation of diabetic foot ulcers is a serious problem. Regenerative medicine, defined as a field that can repair, regenerate or replace cells or tissue, can have a very important role in the treatment of this pathology. Over the years, new protocols to reconstruct β cells to produce insulin have been tried out, solving the problem that characterizes the disease.The diabetic foot ulcer is a very serious complication that is usually localized on pressure points and it can lead to the need to amputate the limb. The diabetic patient is characterized by an impaired ability to heal wounds. Normally, the healing process of a wound follows precise steps, which in the case of a patient suffering from this disease, can be altered. Many studies have shown that regenerative medicine can be a valuable aid in improving wound healing of diabetic patients. Stem cells can be considered an important resource because of their capability of self-renewal and differentiation. Several experiments have shown that transplanting mesenchymal stem cells (MSCs) into the site of the lesion may help in the realization of some steps of the resolution of the wound.